Testing predictions of electron scale turbulent pedestal transport in two DIII-D ELMy H-modes. (13th April 2021) - Guttenfelder, W.; Groebner, R.J.; Canik, J.M.; Grierson, B.A.; Belli, E.A.; Candy, J.
Abstract: In this paper, we present linear and nonlinear gyrokinetic analyses in the pedestal region of two DIII-D ELMy H-mode discharges using the CGYRO code. The otherwise matched discharges employ different divertor configurations to investigate the impact of varying recycling and particle source on pedestal profiles. Linear gyrokinetic simulations find electrostatic ion-scale instabilities (ion temperature gradient and trapped electron modes, ITG–TEM) are present just inside the top of the pedestal with growth rates that are enhanced significantly by parallel velocity shear. In the sharp gradient region, E × B shearing rates are comparable or larger than ion scale growth rates, suggesting the suppression of ITG–TEM modes in this region. Instead, the electron temperature profiles are found to be correlated with and just above the electron temperature gradient (ETG) instability thresholds. Using gradients varied within experimental uncertainties, nonlinear electron-scale gyrokinetic simulations predict electron heat fluxes from ETG turbulence, that when added to neoclassical (NC) ion thermal transport simulated by NEO, account for 30%–60% of the total experimental heat flux. In addition, the NC electron particle flux is found to contribute significantly to the experimental fluxes inferred from SOLPS-ITER analysis. Additional nonlinear gyrokinetic simulations are run varying input gradients to develop a threshold-based reduced model for ETG transport, finding a relatively simple dependence on η e = L ne / L Te . Predictive transport simulations are used to validate this pedestal-specific ETG model, in conjunction with a model for NC particle transport. In both discharges, the predicted electron temperatures are always overpredicted, indicative of the insufficient stiffness in the ETG pedestal model to account for all of the experimental electron thermal transport. In the case of the closed divertor discharge with lower particle source, the predicted electron density is close to the experiment, consistent with the magnitude of NC particle transport in that discharge. However, the density profiles are overpredicted in the open divertor discharge (larger particle source), due to insufficient model transport. The implications for other mechanisms accounting for the remainder of transport in the sharp gradient region in the two discharges are discussed.